2017
DOI: 10.1097/phh.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Pharmacy–Public Health Collaborations Using Pharmacy-Based Point-of-Care Testing Services for Infectious Diseases

Abstract: CLIA-waived POCT services for infectious diseases are a means for pharmacists, public health professionals, and prescribers to collaboratively combat antibiotic resistance and improve community health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…In the future, providing ongoing COVID-19 surveillance to communities by allowing walk-in testing at community pharmacies might be more sustainable and convenient than the large-scale public screening being done as of the summer of 2020. By the fall of 2020, many pharmacies will be offering 1 or more of the following COVID-19 diagnostic services: selling home testing kits, collecting specimens to send to partner laboratories for testing and reporting, collecting specimens for on-site symptomatic testing and reporting, and collecting specimens for point-of-care antibody surveillance ( 31 , 35 , 36 ). The US Department of Health and Human Services has authorized all pharmacists to provide these COVID-19 testing services, overriding state law where it exists ( 37 ).…”
Section: Community Pharmacists’ Response During Covid-19 Pandemicmentioning
confidence: 99%
“…In the future, providing ongoing COVID-19 surveillance to communities by allowing walk-in testing at community pharmacies might be more sustainable and convenient than the large-scale public screening being done as of the summer of 2020. By the fall of 2020, many pharmacies will be offering 1 or more of the following COVID-19 diagnostic services: selling home testing kits, collecting specimens to send to partner laboratories for testing and reporting, collecting specimens for on-site symptomatic testing and reporting, and collecting specimens for point-of-care antibody surveillance ( 31 , 35 , 36 ). The US Department of Health and Human Services has authorized all pharmacists to provide these COVID-19 testing services, overriding state law where it exists ( 37 ).…”
Section: Community Pharmacists’ Response During Covid-19 Pandemicmentioning
confidence: 99%
“…Community-based pharmacist practitioners are well positioned to serve as gatekeepers for antibiotic prescribing due to their considerable training and knowledge of infectious disease pathophysiology, antibiotic indication, dosing, and appropriate length of treatment [72]. In addition to being competent antimicrobial stewards, community-based pharmacist practitioners’ role in curbing antimicrobial resistance is expanding to increase patient access to care through physician-led collaborative practice agreements and CLIA waived POCT [73]. In community pharmacy-based CLIA-waived testing facilities, community-based pharmacist practitioners can screen for and treat acute infectious diseases, such as influenza A/B, Group A streptococcus (GAS) and Helicobacter pylori , decreasing time to therapy for patients [74].…”
Section: Resultsmentioning
confidence: 99%
“…These services, specifically those waived under the Clinical Laboratory Improvement Amendments of 1988, can increase the role pharmacists have in the outpatient setting and improve collaborative services with other providers and public health services. 33 Previous studies have shown the benefits of these services, including one evaluating group A Streptococcus pharyngitis testing in community pharmacies in the Midwest. In total, the study screened 316 patients, with 273 being eligible for testing.…”
Section: Discussionmentioning
confidence: 99%